Entre textos e contextos sobre educação e geografia: reflexões necessárias - Carvalho, Gilvana Fatima (2020)
This is a brief contextualization of the policy Brazilian educational that marked the history of education, showing those contributed at preparation than today result in Base Nacional Comum Curricular (BNCC). To we discuss this theme is necessary understand that the education is result of the historic, economic, political, social and cultural context whereby was thought and produced. Understand these meander, mainly, political and economic we allowed shed light in our objective: which were the path taken for Brazilian education since mid-1930 until the implantation of BNCC, as well as apprehension the historic context whereby the educational policy developed. Our basic theoretical foundation was major to understand our objective. For this purpose, we used the works of Romanelli (2014), Saviani (2013), Ruy Moreira (1982), Vesentini (1989), Milton Santos (1993), Straforini (2008), Freire (2011), Libâneo (1986), among others. We realized a bibliographic documental research to better expatiate on our thematic, it’s current and it is constant change, so the interests spin around of education weren’t statics. Thus, is essential we understand the development’s move of the curriculum and documents education, so directs the country paths. To purposes organization we divided the research in 03 (three) chapters. In the first chapter we point the main Brazilian educational policy since 1930 until 1988, are these years the majority of documents that emphasize the need of a homogeneous curriculum and/or a Base Comum Curricular. Furthermore, in this period have the manager’s government plans for support the public policies development as to education as to the other sectors. In the other chapter expatiate on re-democratization processing that marked significant changes to educational landscape. Later we approach as the Geography presents in some documents orienting, as in Parâmetro Curricular Nacional (PCN). The second chapter we highlight the Neoliberalism influence on educations, in other words, we demonstrated the commercialization of the education and your impacts at educational policy in Brazil. In quite that context we intend articulate the educational measures associated the Neoliberalism to Geography education. In last chapter expatiate on Base Nacional Comum Curricular (BNCC), articulates to educational policy previous that affect the curriculum and, finally, we indicate some notes of BNCC in Geography education. This research caused the reflection and concern respect for understanding of complex relationships that around the education. Although been difficult, it is important to people’s life and to country development.